Danger Of Onlıne Gamblıng Usıng 2D Anımatıon And Its Acceptance Usıng UTAUT - Rainal Agus Setiawan; Jimmy Pratama (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
At this time, technological developments are unavoidable. Moreover, technological developments in learning media play an important role in educating the public. One of them is learning media with animated videos. This study aims to determine the effect of 2D animated video about the dangers of online gambling on teenagers in Batam City. The author uses the Multimedia Development Life Cycle (MDLC) method in designing 2D animated videos. The author also used quantitative approach by distributing questionnaires through Google Form with a total of 400 respondents. The result of this research shows that the indicators tested are relatively positive. For the measurement model, confirm that all outer loading values are â‰¥0.65. CR values range from 0.839 to 0.877. The AVE value is between 0.597 to 0.692. Therefore, convergent validity has been met in this case study. For discriminant validity has also been met. The results of the research on the structural model confirmed that Hedonic Motivation (HM) had a significant positive effect, followed by Effort Expectancy (EE), and Students' Innovativeness (SINN) in order. However, Performace Expectancy (PE), Social Influence (SI), Facilitating Conditions (FC), Learning Value (LV) showed that there was no significant effect on Behavior Intention of Animation Usage (BI) in animation usage.